ESTIMASI NILAI RIPITABILITAS BOBOT SAPIH DAN MOST PROBABLE PRODUCING ABILITY KAMBING SABURAI BETINA DI KELOMPOK TANI GUYUP RUKUN KECAMATAN SUMBEREJO, KABUPATEN TANGGAMUS - Dennis Mulya Harpangestu; Akhmad Dakhlan; Dian Kurniawati; Arif Qisthon (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2022)
This study aimed to determine the repeatability estimate of weaning weight and the Most Probable Producing Ability (MPPA) of female Saburai goats in the Guyup Rukun Farm Group in Sumberejo District, Tanggamus Regency which was conducted in November 2020. The method used in this study was a survey method using 50 Saburai does that had given birth twice from 2016-2020. The observed variables were birth weight, age of the dam at giving birth, weaning age, type of birth, sex and weaning weight at the first and second parity. Weaning weights were corrected for sex, the age of the dam, weaning age of 90 days, and birth type. The repeatability estimate was calculated using interclass correlation method. The Repeatability estimate then was used to estimate the MPPA of Saburai does. The results showed that the repeatability estimate of weaning weight of Saburai goat was 0.72 (high category). The average MPPA of weaning weight for Saburai does was 16.41±0.92 kg with the highest MPPA was 18.92±0.92 kg and the lowest MPPA was 14.96±0.92 kg. There were 18 does with MPPA values ​​above the average of the population in the farmer group with livestock code KI2, KI3, KS3, KI6, KI4, KI5, JW2, MD3, KI1, SK1, MG1, TW2, KS4, SY3, SK2, MG5, SR3, and KT3. Keywords: Most Probable Producing Ability, Repeatability estimate, Saburai Goat, Weaning Weight